2005
DOI: 10.1080/08870440512331317634
|View full text |Cite
|
Sign up to set email alerts
|

Finding benefit in breast cancer: Relations with personality, coping, and concurrent well-being

Abstract: Cancer patients experience positive as well as adverse consequences from cancer diagnosis and treatment. The work reported here was part of an effort to characterize the experiences of benefit finding in breast cancer patients. A sample of 230 early-stage breast cancer patients completed a set of benefit finding items in the year post-surgery. This measure was then related to measures of concurrent coping, several aspects of psychosocial well-being, demographic variables, and several other personality traits. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
213
3
24

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(271 citation statements)
references
References 73 publications
31
213
3
24
Order By: Relevance
“…Some other studies reached similar conclusions in the assessment of the disease over time [12,[54][55][56][57].…”
Section: Discussionsupporting
confidence: 55%
“…Some other studies reached similar conclusions in the assessment of the disease over time [12,[54][55][56][57].…”
Section: Discussionsupporting
confidence: 55%
“…This was the sample reported in Urcuyo et al (2005; see that article for details on recruitment). For reasons unrelated to this report, the study examined variation across time since surgery.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…In psycho-oncological research, HRQoL is sometimes positively related to PTG (Bower et al 2005;Penedo et al 2006;Urcuyo et al 2005). For example, Lelorain et al (2010) demonstrated that mental health and vitality subscales of overall quality of life were significantly positively related to PTG.…”
mentioning
confidence: 99%